1988
DOI: 10.1007/bf00915889
|View full text |Cite
|
Sign up to set email alerts
|

Substance-P-like levels in inflammatory exudates

Abstract: Levels of SP-like immunoreactivity were assessed by enzyme immunoassay in exudates induced in the rat by intrapleural injection of either calcium pyrophosphate (CaPP) or carrageenan. SP-like levels increased during the first hour, up to approximately 2 ng/ml, and remained significantly higher than control values from 1 to 6 h after the induction of pleurisy by CaPP. With carrageenan as the irritant, SP-like levels rose during the first 4 h, up to 3 ng/ml, and remained significantly higher than control values f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

1989
1989
2002
2002

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…Recent studies have suggested that the ultimate severity of the resulting pancreatitis may be determined by events that occur subsequent to acinar cell injury including inflammatory cell recruitment and activation and the generation and release of cytokines and other chemical mediators of inflammation (19)(20)(21). Although neurogenic factors have been shown to play an important role in a variety of other inflammatory processes (1,2,6,(22)(23)(24)(25)(26), the potential role of neurogenic factors as regulators of the severity of acute pancreatitis has not been previously evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have suggested that the ultimate severity of the resulting pancreatitis may be determined by events that occur subsequent to acinar cell injury including inflammatory cell recruitment and activation and the generation and release of cytokines and other chemical mediators of inflammation (19)(20)(21). Although neurogenic factors have been shown to play an important role in a variety of other inflammatory processes (1,2,6,(22)(23)(24)(25)(26), the potential role of neurogenic factors as regulators of the severity of acute pancreatitis has not been previously evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…These results provide evidence that LPMs must be considered as a source of SP in C. difficile toxin A-mediated enteritis. Several other studies show that immune and inflammatory cells synthesize and release SP, including rat peritoneal macrophages (30), the murine macrophage cell line P388D1 (44), mouse granuloma eosinophils (16), and human eosinophils (45). Moreover, Bost et al (30) demonstrated that stimulation of rat peritoneal macrophages with LPS increased the abundance of SP mRNA.…”
Section: Discussionmentioning
confidence: 99%
“…Mast cells (10), polymorphonuclear leukocytes (11), T lymphocytes (12,13), and macrophages (14) can respond to SP, indicating that the effects of SP during inflammation may be mediated by direct activation of these cells. SP levels are also elevated in inflamed tissues (15)(16)(17), and increased binding sites for SP have been demonstrated at sites of inflammation in conditions such as arthritis (18) and Crohn disease (19). In regard to intestinal inflammation, studies from our laboratory indicate that SPcontaining sensory neurons are involved in the enterotoxic effects of Clostridium difficile toxin A, the causative agent of antibiotic-associated enterocolitis in animals and humans (20).…”
mentioning
confidence: 99%
“…The peptidergic sensory nerve fibers take part in nociception and peptide-mediated neurogenic inflammation, both in normal and injured tissue (Heyeraas et al, 1994;McMahon and Koltzenburg, 1990;Kruger, 1988;Jancs6 et al, 1967). The sensory neuropeptides substance P (SP) and calcitonin gene-related peptide (CGRP) are released after sensory nerve stimulation (Heyeraas et al, 1994;Olgart et al, 1977) and at local sites of inflammation (Tissot et al, 1988).…”
Section: Troductionmentioning
confidence: 99%